Bias in Stroke Evaluation: Rethinking the Cookie Theft Picture. Issue 6 (6th May 2022) - Steinberg, Amy; Lyden, Patrick D.; Davis, Arielle P.
Abstract : Despite a current emphasis on equity in stroke care, one of the most common stroke assessment tools that is used both nationally and internationally, includes an anachronistic image that projects cultural, linguistic, and socioeconomic bias. This image, titled The Cookie Theft picture, is included in the National Institutes of Health Stroke Scale and was originally developed in 1972. Now, 50 years later, it does not reflect our current diverse, linguistically rich, and multicultural patient population.